2021
DOI: 10.3389/fanim.2021.759147
|View full text |Cite
|
Sign up to set email alerts
|

Automated Individual Cattle Identification Using Video Data: A Unified Deep Learning Architecture Approach

Abstract: Individual cattle identification is a prerequisite and foundation for precision livestock farming. Existing methods for cattle identification require radio frequency or visual ear tags, all of which are prone to loss or damage. Here, we propose and implement a new unified deep learning approach to cattle identification using video analysis. The proposed deep learning framework is composed of a Convolutional Neural Network (CNN) and Bidirectional Long Short-Term Memory (BiLSTM) with a self-attention mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Qiao et al [40] proposed and implemented a unified deep learning method for bovine recognition based on video analysis, which is composed of convolutional neural networks and bidirectional long short-term memory (BiL STM) with self-attention mechanism. Lima Weber et al [41] purpose to identify cattle breeds using convolutional neural networks.…”
Section: Cnn Identification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiao et al [40] proposed and implemented a unified deep learning method for bovine recognition based on video analysis, which is composed of convolutional neural networks and bidirectional long short-term memory (BiL STM) with self-attention mechanism. Lima Weber et al [41] purpose to identify cattle breeds using convolutional neural networks.…”
Section: Cnn Identification Methodsmentioning
confidence: 99%
“…We evaluated the performance of four different convolutional neural network models, namely Mask R-CNN, Attention-BiLSTM [40]…”
Section: B Test Environment and Parameter Settingsmentioning
confidence: 99%
“…The recent advancements in artificial intelligence have made it even easier to analyze animal behavior in videos using machine vision and machine learning (139). The development of predictive models such as Convolutional Neural Network (CNN) and Long Short-Term Memory (LSTM) based on modern machine techniques are helpful in livestock research (139,140). It was shown that the development of a recurrent neural network (RNN) model with an LSTM could classify cattle behavior in a reasonable manner (141).…”
Section: Machine and Deep Learning Approaches In Livestock Researchmentioning
confidence: 99%
“…It was shown that the development of a recurrent neural network (RNN) model with an LSTM could classify cattle behavior in a reasonable manner (141). Recently, CNN and Bidirectional Long Short-Term Memory (BiLSTM) were used for video-based identification of individual cattle (140), and C3D-ConvLSTM (Convolutional 3D-Convolutional Long Short-Term Memory) based model was used for cow behavior classification over 86% accuracy (142).…”
Section: Machine and Deep Learning Approaches In Livestock Researchmentioning
confidence: 99%
“…One such approach involved evaluating wearable devices and cameras attached to cattle bodies for behavior monitoring [ 23 ]. Another study proposed a deep-learning-based approach for cattle identification using video analysis [ 24 ]. This approach utilized convolutional neural networks (CNN) and bidirectional long short-term memory (BiLSTM) with a self-attention mechanism, implemented to monitor 50 individuals.…”
Section: Introductionmentioning
confidence: 99%